Bean program 1978 report - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1979)
Emphasis has been placed on the screening of hybrid selections for resistance to rust, anthracnose, BCMV and Empoasca sp., yield and sensitivity to photoperiod. A total of 1464 materials (937 selections from the breeding program) were screened in the Bean Team Nursery and 700 (200 breeding selections) in the Preliminary Yield Trial. Results from the latter demonstrated major gains in yield among colored materials and a very high proportion of lines resistant to BCMV. Many lines demonstrated multiple-disease resistance. In 1978, 150 International Bean Yield and Adaptation nurseries (88 color, 62 black) were distributed to 34 countries. Rust, BGMV and BCMV nurseries were also distributed. Other major advances include initiation of a breeding program for climbing cv. to be grown in association with maize, establishment of temp conditions likely to limit N fixation and identification of cv. tolerant to low soil P. Microregions of bean production in L.A. were identified and an agroclimatology survey initiated. On-farm trials showed that low-cost cultural practices could increase yields 50 percent. Breeding work for resistance to anthracnose, angular leaf spot and other conditions common to cooler climates was intensified. (CIAT)